69.7k views
5 votes
Help with this problem pls

Help with this problem pls-example-1

1 Answer

1 vote

nswer:


(f\circ g)(x)\text{ = 4x}^2+26x+29

Step-by-step explanation:

ere, we want to solve the given composuite function

What we have to do is to replace the x in f(x) with the entirety of g(x)

We have that as:


\begin{gathered} (f\circ\text{ g\rparen\lparen x\rparen = f\lparen g\lparen x\rparen\rparen} \\ =\text{ f\lparen2x+9\rparen} \end{gathered}

Now, we replace x in f(x) with 2x+9 as stated

We have that as:


\begin{gathered} f(2x+9)\text{ = \lparen2x+9\rparen}^2-5(2x+9)\text{ - 7} \\ f(2x+9)\text{ = 4x}^2+36x+81-10x-45-7 \\ f(2x+9)\text{ = 4x}^2+36x-10x+81-45-7 \\ f(2x+9)\text{ = 4x}^2+26x+29 \end{gathered}